MATERIAL OBJECTS AND FORMAL OBJECTS ISLAMIC EDUCATION MANAGEMENT SCIENCE - Moh. Soleh; Rohman; Tuti Asiyah; Abdul Muin (INDOPEDIA (Jurnal Inovasi Pembelajaran dan Pendidikan), 2023)
Empirical nature is measurable and repetitive like a person who throws a stone so wherever it falls it will remain a stone. This is very different from the natural mind, whether it is proven or not that is important is rational. Likewise with the possibility, namely the object being targeted is what may or may not happen. This study discusses material objects and formal objects in Islamic education management science. The method used in this research is literature review and data analysis because the data collected is qualitative data, namely in the form of expressions of thinkers and experts in Islamic education management. The results of this study indicate that a material object is something that is the object of thought, something that is researched or something that is studied. The formal object is a way of viewing, a way of conducting a review by a scientist or a researcher on a material object and the principles it uses.